Interaction between toxic dinoflagellate Alexandrium catenella exposure and disease associated with herpesvirus OsHV-1μVar in Pacific oyster spat Crassostrea gigas - Lassudrie, M; Soudant, P; Nicolas, JL; Fabioux, C; Lambert, C; Miner, P; Le Grand, J; Petton, B; Hégaret, H (2015)
© 2015 Elsevier B.V. Blooms of toxic dinoflagellates can co-occur with mass mortality events associated with herpesvirus OsHV-1. μVar infection that have been decimating Pacific oyster Crassostrea gigas spat and juveniles every summer since 2008 in France. This study investigated the possible effect of a harmful dinoflagellate, Alexandrium catenella, a producer of Paralytic Shellfish Toxins (PSTs), upon the oyster spat-herpesvirus interaction. Oyster spat from a hatchery were challenged by cohabitation with oysters contaminated in the field with OsHV-1. μVar and possibly other pathogens. Simultaneously, the oysters were exposed to cultured A. catenella. Infection with OsHV-1. μVar and PST accumulation were measured after 4 days of experimental exposure.Exposure to Alexandrium catenella modified the host-pathogen interaction by reducing prevalence of OsHV-1. μVar infection. In addition, oysters challenged with OsHV-1. μVar and possibly other pathogens from the environment accumulated smaller amounts of PSTs than unchallenged oysters. Three possible mechanisms are suggested by these results: (i) possible direct interactions between A. catenella and herpesvirus (or associated pathogens) could reduce viral transmission and algal availability for oyster consumption; (ii) oyster feeding behavior or digestive functions may have been altered, thus decreasing both uptake of viral particles and consumption or digestion of toxic algae and consequent toxin accumulation; (iii) immuno-activation by A. catenella could enhance defense efficiency against OsHV-1. μVar infection. These findings suggest further research on relationships between OsHV-1. μVar and toxic dinoflagellates and their combined effects upon disease transmission and proliferation processes, as well as on oyster physiological and immunological involvement in this complex, tripartite interaction.